Purification and properties of two deoxyribonucleases of Pseudomonas aeruginosa. - Miller, R V (1976)
A survey of the major deoxyribonucleases in Pseudomonas aeruginosa strain PAO was undertaken. Two activities predominated in Brij-58 lysates of this organism. These have been purified from contaminating nuclease activities, and some of their properties have been elucidated. The first was a nuclease that degraded heat-denatured deoxyribonucleic acid (DNA) to mono- and dinucleotides. The activity of this enzyme was confined to single-stranded DNA, and 100% of the substrate was hydrolyzed to acid-soluble material. The Mg2+ optimum is low (1 to 3mM), and the molecular weight is 6 X 10(4). The second predominant activity was an adenosine 5'-triphosphate (ATP)-dependent deoxyribonuclease. This enzyme had an absolute dependence on the presence of ATP Mg2+ concentrations of approximately 10 mM. Five moles of ATP was consumed for each mole of phosphodiester bonds cleaved. The acid-soluble products of the reaction consisted of short oligonucleotides from one to six bases in length. Only 50% of the double-stranded DNA was rendered acid soluble in a limit digest. The molecular weight of this enzyme is 3 X 10(5). The observation of these enzymes in P. aeruginosa is consistent with the possibility that recombinational pathways similar to those of Escherichia coli are operating in this organism.